SARS‐COV‐2–associated coagulopathy and thromboembolism prophylaxis in children: A single‐center observational study. (23rd December 2020) - Del Borrello, Giovanni; Giraudo, Isaac; Bondone, Claudia; Denina, Marco; Garazzino, Silvia; Linari, Claudia; Mignone, Federica; Pruccoli, Giulia; Scolfaro, Carlo; Spadea, Manuela; Pollio, Berardino; Saracco, Paola
Abstract: Background: Multiple investigators have described an increased incidence of thromboembolic events in SARS‐CoV‐2–infected individuals. Data concerning hemostatic complications in children hospitalized for COVID‐19/multisystem inflammatory syndrome in children (MIS‐C) are scant. Objectives: To share our experience in managing SARS‐CoV‐2–associated pro‐coagulant state in hospitalized children. Methods: D‐dimer values were recorded at diagnosis in children hospitalized for SARS‐CoV‐2–related manifestations. In moderately to critically ill patients and MIS‐C cases, coagulation and inflammatory markers were checked at multiple time points and median results were compared. Pro‐thrombotic risk factors were appraised for each child and thromboprophylaxis was started in selected cases. Results: Thirty‐five patients were prospectively enrolled. D‐dimer values did not discriminate COVID‐19 of differing severity, whereas were markedly different between the COVID‐19 and the MIS‐C cohorts. In both cohorts, D‐dimer and C‐reactive protein levels increased upon clinical worsening but were not accompanied by decreased fibrinogen or platelet values, with all parameters returning to normal upon disease resolution. Six patients had multiple thrombotic risk factors and were started on pharmacological thromboprophylaxis. No deaths or thrombotic or bleeding complications occurred. Conclusions: COVID‐19 pediatric patients show mildly altered coagulation and inflammatory parameters; on the other hand, MIS‐C cases showed laboratory signs of an inflammatory driven pro‐coagulant status. Universal anticoagulant prophylaxis in hospitalized children with SARS‐CoV‐2–related manifestations is not warranted, but may be offered to patients with other pro‐thrombotic risk factors in the context of a multi‐modal therapeutic approach.